Наукові засади формування якості плодових тіл їстівних грибів родів Pleurotus, Cyclocybe, Flammulina та Calocybe: реферат дисертації… д-ра с.-г. наук - Бандура, Ірина Іванівна; Bandyra, Iryna (My University, 2023)
The dissertation on competition of a scientific degree of the doctor of agricultural sciences on a specialty 06.01.06 – vegetable growing (20 Agrarian sciences and food). Uman National University of Horticulture, Uman, 2022. The qualitative scientific work is substantiated scientific bases for formation the quality of xylotrophic mushroom species with proved food and medicinal value: oyster mushroom, lung mushroom, king oyster mushroom, lemon or gold oyster mushroom, winter needle mushroom, poplar mushroom or “piopinno” and tropical exotic species “milky mushroom”. In this work, the technological components of the cultivation process of the above species were investigated to obtain fruiting bodies with predictable qualitative characteristics by the requirements of post-harvest procedures. A comprehensive screening of 24 strains under industrial production conditions, based on the results of which technical characteristics of productivity, parameters of phenotypic traits, biochemical contains of fruiting bodies, yield ratios of semi products in postharvest operations and primary processing were determined, allowing selection of the most promising strains for industrial implementation. The necessity of achieving substrate selectivity by balancing the composition of organogenic and essential elements, elimination of pathogenic microorganisms and creating a certain structure of substrates as the most crucial factor in the formation of yield quality of xylotrophic species is proven. The individual requirements of the studied cultivars for the degree of substrate electivity, their biological efficacy, and the nature of changes in the biochemical composition of the yield obtained in accordance with the composition of substrate compositions were determined. The possibility of predicting the quality phenotypic and biochemical characteristics of cultivars through the necessary technical operations has been revealed: making substrate units of the required mass, forming the fruiting zone through the perforations of a given size, or opening area, spatial position on the shelves, applying the best height of the cover soil, and conducting scratching technic. A general trend of protein decreases to 8.6% and increase of ash elements amount to 4.9% of dry matter was revealed as well as the significant increase of the bioactive endopolysaccharides amount (from 6 to 10% in dry matter) at the achievement of biological ripeness by fruiting bodies. The fact of increase in a factor of a half-finished product yield after blanching of fruiting bodies of biological ripeness by 3-6% in comparison with the processing of raw materials collected at a level of technical ripeness is fixed. The quantitative and qualitative analysis of microbiological successions in the air of premises where P. ostreatus was cultivated for a long time was conducted and the dynamics of the increase of CFU titer on the surface of P. ostreatus fruiting bodies depending on the state of microbiological contamination of cultivation premises (y=4148071+299×x) were calculated. The economic benefits of the developing adaptation technologies and implemented technical operations was improved. The variants of definition of profit in mushroom growing using technical cards and the solution of a problem of optimization of manufacture of multicomponent substrates with the balanced formula and the minimum cost are offered.
Keywords: mushroom industrial cultivation; quality of mushrooms; biological efficiency; morphology of fruiting bodies; milky mushroom; poplar mushroom; winter mushroom; king oyster mushroom; lung oyster mushroom; gold oyster mushroom; modelling of substrate compositions; oyster mushroom